Notes on floral traits and gender expression of Dryas octopetala under a simulated environmental change - Wada , Naoya; Kanda, Hiroshi (National Institute of Polar Research, 2000)
P(論文) This study presents empirical data for variations of floral traits and gender expression in Arctic Dryas octopetala L. under a simulated environmental amelioration using an open-top chamber (OTC). The short-term experiment (from 8 August 1997 to 2 August 1998) demonstrated in Ny-Alesund, Svalbard that dry weights of gynoecium, peduncle, and hermaphrodite flowers were significantly heavier, whereas petal and androecium weight were significantly lighter in OTC-manipulated shoots than in controls. As a result, "femaleness" (dry-weight allocation to the female organs) showed a significantly higher value in OTC-manipulated shoots as compared to the controls. Moreover, femaleness was significantly positively correlated with flower weight both in OTC-manipulated and control shoots. Thus, it was experimentally demonstrated that the gender as a reproductive effort of D. octopetala flowers changed from male- to female-biased expression under a less stressful condition. departmental bulletin paper